A Practitioner's Guide to Innovation Policy : Instruments to Build Firm Capabilities and Accelerate Technological Catch-Up in Developing Countries - Cirera, Xavier (World Bank, Washington, DC, 2020)
This practitioner’s guide, a companion volume to The Innovation Paradox picks up where the previous report left off. It aims to help policy makers in developing countries better formulate innovation policies. It does so by providing a rigorous typology of innovation policy instruments, including evidence of impact—and more importantly, the critical conditions in terms of institutional capabilities to successfully implement these policy instruments in developing countries. The guide aims to help fill a knowledge gap by presenting not only leading-edge empirical evidence about and practical experience with innovation policy, but also systematically discussing the market and system failures that hold back innovation in developing countries.